2013
DOI: 10.1124/mol.113.089649
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Functionally Selective κ-Opioid Receptor Scaffolds

Abstract: The k-opioid receptor (KOR)-dynorphin system has been implicated in the control of affect, cognition, and motivation, and is thought to be dysregulated in mood and psychotic disorders, as well as in various phases of opioid dependence. KOR agonists exhibit analgesic effects, although the adverse effects produced by some KOR agonists, including sedation, dysphoria, and hallucinations, have limited their clinical use. Interestingly, KOR-mediated dysphoria, assessed in rodents as aversion, has recently been attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 51 publications
2
116
2
Order By: Relevance
“…Such studies are particularly important given reports that biased signaling at κOR can distinguish the aversive effects of κOR agonists from the antinociceptive effects (8). Consistent with this, studies have shown that, whereas Sal A appears to be an unbiased ligand based on G-protein activation and β-arrestin recruitment assays, a structural derivative, RB-64, appears to exhibit G-protein-biased activity (32). Studies with this compound argue for a contribution of the G-protein pathway in κOR-mediated analgesia and aversion and of other pathways on κOR-mediated motor coordination, sedation, and anhedonia (33).…”
Section: Discussionmentioning
confidence: 65%
“…Such studies are particularly important given reports that biased signaling at κOR can distinguish the aversive effects of κOR agonists from the antinociceptive effects (8). Consistent with this, studies have shown that, whereas Sal A appears to be an unbiased ligand based on G-protein activation and β-arrestin recruitment assays, a structural derivative, RB-64, appears to exhibit G-protein-biased activity (32). Studies with this compound argue for a contribution of the G-protein pathway in κOR-mediated analgesia and aversion and of other pathways on κOR-mediated motor coordination, sedation, and anhedonia (33).…”
Section: Discussionmentioning
confidence: 65%
“…Several reports have demonstrated KOR ligand functional selectivity in HEK cells Rives et al, 2012;Schattauer et al, 2012;White et al, 2014White et al, , 2015 and immortalized astrocytes (McLennan et al, 2008), and it has been suggested that ligands biased for G protein activation may be more effective analgesics (Bruchas et al, 2007a;White et al, 2015). Although well established in heterologous expression systems, there are relatively few studies that have established the functional selectivity of ligands toward cellular signaling pathways in physiologically relevant systems (Bailey et al, 2009;Melief et al, 2010;Schmid and Bohn, 2010;Bosier et al, 2012;Morgan et al, 2014;White et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, their clinical utility is hampered by an array of undesirable side effects, including dysphoria, sedation, diuresis, hallucination, and depression (Pfeiffer et al, 1986;Togashi et al, 2002;Land et al, 2008;Van't Veer and Carlezon, 2013). Interestingly, it has been proposed that the dysphoric component of KOR agonism is mediated via a process involving arrestins (Bruchas et al, 2006;Redila and Chavkin, 2008), suggesting that G protein biased KOR agonists may deliver the desired analgesic effect while circumventing deleterious mood disturbances Zhou et al, 2013;White et al, 2014).…”
Section: Translating Biasmentioning
confidence: 99%